The Influence of Food Quality and Service Quality on Repurchase Intention Through Customer Satisfaction - Edgar, Thomas; Ellitan, Lena (Journal of Entrepreneurship and Business, 2024)
Purpose: This research aims to analyze the influence of food quality and service quality on repurchase intention through customer satisfaction in Sambal Bakar in Surabaya. Method: This research use quantitative causal design. A total of 137 respondents aged above 17 participated in this study. The analysis method employed was Structural Equation Modeling-Partial Least Square (SEM PLS). Result: The research results indicate that both food quality and service quality have a positive and significant impact on customer satisfaction. Customer satisfaction, in turn, significantly and positively influences repurchase intention, affirming the crucial contribution of customer satisfaction to the intention to revisit. Furthermore, both food quality and service quality significantly and positively affect repurchase intention, emphasizing that service quality makes a strong contribution to customers' intention to return.